THE IMPORTANCE AND ROLE OF HEALTH WORKERS IN THE RELATIONSHIP WITH THE PUBLIC IN THE FUNCTION OF RAISING AWARENESS ABOUT ONCOLOGICAL DISEASES - Sinanović, Šćepan; Milovanović, Olivera; Kilibarda, Tatjana; Prodović, Tanja; Đukanović, Nina; Potić, Srećko; Martinović, Biljana; Sekulić, Jelena; Bubanj, Saša (Acta medicae Medianae, 2023)
Public relations represent a management function and should establish mutual quality relations between the health institution and the public, on which the success of the organization depends. Public relation is a complex communication process, which includes the activities of a healthcare organization, aimed at developing cooperation with target groups, which can be internal and external. Good communication contributes to doctors and medical staff maintaining their professionalism at a high level, while following the principles of medical ethics, which greatly improves the quality of life of oncology patients. Communication is a key element of the patient’s trust in the medical staff, and it plays a vital role in the treatment of oncology patients. Dialogue through which support is provided is an extremely valuable resource and can be the most important (sometimes the only) element of patient care. The basic idea of an effective therapeutic dialogue is that the patient should get the impression that someone has heard and understood his fears and worries, in which the nurse’s role is essential because she spends most of her time with the patient. It may happen that some of the problems can be solved, that some emotional moments can be overcome or that some needs can be satisfied, but even when there is no solution, the simple act of dialogue will reduce the patient’s discomfort.